ARTIFICIAL INTELLIGENCE FROM THE PERSPECTIVE OF EDUCATIONAL PHILOSOPHY: OPPORTUNITIES, CHALLENGES, AND ETHICAL IMPLICATIONS - Miftahudin; Muntaha Mahfud; Aina Sufya Fuaida; Rudini; Muhlisin (PT. Cadas Insan Madani, 2026)
The rapid development of Artificial Intelligence (AI) has transformed various sectors of society, including education, by introducing innovative approaches to teaching, learning, assessment, and educational management. While AI offers significant opportunities to improve learning effectiveness, personalize educational experiences, and enhance institutional efficiency, it also raises fundamental philosophical and ethical questions concerning the nature of knowledge, the role of educators, human autonomy, justice, and moral responsibility. This study aims to examine Artificial Intelligence from the perspective of educational philosophy by analyzing its opportunities, challenges, and ethical implications in contemporary education. The research employs a qualitative library research approach through a comprehensive review of scholarly books, peer-reviewed journal articles, policy documents, and international reports related to artificial intelligence, educational philosophy, and educational ethics. The collected data were analyzed using descriptive content analysis to identify major philosophical themes and ethical issues associated with AI integration in education. The findings reveal that Artificial Intelligence has considerable potential to enhance personalized learning, improve educational accessibility, support data-driven decision-making, and facilitate innovative pedagogical practices. However, AI implementation also presents significant challenges, including algorithmic bias, data privacy concerns, digital inequality, the declining role of human interaction in learning, and the need to preserve critical thinking and moral development. From the perspective of educational philosophy, AI should be regarded as a complementary tool that supports, rather than replaces, the essential role of teachers in fostering intellectual growth, ethical reasoning, and holistic human development. The study concludes that the successful integration of AI into education requires a balanced approach that combines technological innovation with humanistic values, ethical governance, and philosophical reflection. This research contributes to the growing discourse on educational philosophy by providing a conceptual framework for understanding the responsible and ethical implementation of Artificial Intelligence in contemporary educational systems.